SEBAB DAN AKIBAT STRES, DEPRESI DAN KECEMASAN SERTA PENANGGULANGANNYA - Jamil Jamil (STIT AL-AMIN KREO TANGERANG, 2018)
Psychologically, humans often suffer from various disorders and mental illnesses, such as stress, depression, anxiety, envy, jealousy, sorrow unreasonable, arrogant and many others are. Challenges and struggles of life as well as moral and ethical values change, at certain conditions can lead to tension stress. Stress is part of life that cannot be avoided. Therefore, what we have to do is arrange life so that stress does not cause a reaction, such as physical or psychological complaints. This is called distress